Balkanization of Caucasus: case study of Georgia - Prebilič, Vladimir (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
Although the term and phenomena of balkanization is internationally well-known, excepted within international relations and diplomatic circles, some peculiarities are interesting even for further analysis and discussion. This article underlines some of them and proves that many of them can be traced down in different areas all over the world. Specifics like secession, accompanied by inter- and intrastate conflicts based on ethnic and religious grounds, huge pressure on the civil population expressed in war crimes, genocide and ethnic cleansing, enormous economical devastation of the country and very low level of democracy denoted the collapse of Socialist Federative Republic of Yugoslavia. As the consequence the term balkanization got the final outlook . Analysis of different events after collapse of Soviet Union in Southern Caucasus may be compared, to a certain degree, to those on the territory of former Yugoslavia. Based on this and many other facts article offers new perspective in better comprehension and may enable us to predict further development of the international relations regarding the Southern Caucasus region.
Keywords: Sovjetska zveza; Georgia; Gruzija; geopolitika; balkanizacija; etnični konflikti; mednarodni odnosi; narodnostno vprašanje